Pengaruh Celebrity Endorse Dan Kualitas Produk Terhadap Minat Beli (Studi Kasus Pengguna Skincare Ms Glow Pada Mahasiswa UIN Raden Intan Lampung) - Regita Wulan Ramadhani (Dinar Islamic Review, 2023)
Celebrity endorse is one of the most popular methods in the world, using celebrities that are attractive, have high popularity and can be trusted by the intended public to make the product being promoted known, known and desirable. Efforts made by the company in the form of advertising and celebrity endorse aimed at consumer purchasing decisions in determining and choosing wardah's cosmetics is not an instant thing to happen. The desire for someone to buy something requires a stimulus and stimulation arising from external or internal. This type of research used is quantitative research. The samples in this study were 40 respondents who were taken from consumers skincare ms glow students of the faculty of economics and business islam state university of raden intan lampung. Data collection methods by questionnaire.